Assessing the Deep Carbon Release in an Active Volcanic Field Using Hydrochemistry, δ13CDIC and Δ14CDIC. Issue 4 (12th April 2023) - Zhong, Jun; Wang, Linan; Caracausi, Antonio; Galy, Albert; Li, Si‐Liang; Wang, Wanfa; Zhang, Maoliang; Liu, Cong‐Qiang; Liu, Guo‐Ming; Xu, Sheng
Abstract: Volcanic activities have great implications on the geological carbon cycle, and ascertaining the deep carbon contribution in the Earth's surface that runs along the volcanic edifices is important to understand the relationship between solid Earth degassing and global climate change. This study reports analytical results of major dissolved ions concentrations, carbon isotopic compositions (δ 13 CDIC and Δ 14 CDIC ) of dissolved inorganic carbon (DIC) of rivers, cold springs, and hot springs from Changbaishan volcanic area, Northeast China. The hydrothermal fluids had a significant impact on solutes budgets, as well as carbon isotopes for the rivers. The changes in concentrations of major ions are mainly controlled by mixing of high‐temperature water/rock interaction and low‐temperature water/rock interaction, and low‐temperature water/rock interaction can be explained by the change of chemical composition between volcanic cone (trachyte) and basaltic shield. Because Δ 14 CDIC is conservative to CO2 outgassing, we used Δ 14 CDIC to figure out the contributions of deep carbon and surface carbon. While δ 13 CDIC is sensitive to CO2 outgassing, we thus estimated the minimum deep CO2 outgassing yield (1.24 × 10 4  t C yr −1 ) based on DIC flux corrected for outgassing by a Rayleigh model. In the Changbaishan volcanic area, deep carbon release flux was higher than CO2 consumption flux by silicate weathering, while the deep CO2 outgassing flux was an underestimate, consistent with the hypothesis that deep CO2 release regulates climate on geological timescales. This study calls for a better understanding of the effects of volcanic activities on Earth's surface carbon cycling, which has great implications on studying global climate change. Plain Language Summary: The balance between volcanic degassing and silicate weathering may control the atmospheric CO2, regulating long‐term global climate. Volcanic areas have attracted large amounts of attentions, because of its intricate effects on atmospheric CO2 . We investigated water chemistry, δ 13 CDIC and Δ 14 CDIC in Changbaishan volcanic area to understand carbon biogeochemical processes in volcanic areas. In most previous studies, δ 13 CDIC was used to trace the sources of DIC in volcanic areas, but this study evidenced that δ 13 CDIC is highly controlled by CO2 outgassing, bringing great uncertainties on source discrimination. Δ 14 CDIC is non‐sensitive to CO2 outgassing, so we used Δ 14 CDIC to trace the sources of DIC. Based on the Rayleigh fractionation model, δ 13 CDIC was used to estimate the minimum CO2 outgassing fluxes in this study area. At last, we evaluated the net carbon budget concerning deep carbon release and silicate weathering, and found that deep carbon release flux was higher than CO2 consumption flux by silicate weathering. This study highlights the effects of deep carbon release on Earth's surface and provides mechanistic insights into carbon biogeochemical processes in volcanic areas. Key Points: The water chemical compositions and isotopic compositions of DIC varied in a wide range in Changbaishan volcanic rivers The hydrothermal fluids had a significant impact on solutes budgets, as well as carbon isotopes for the volcanic rivers Deep carbon release flux was higher than CO2 consumption flux by silicate weathering in Changbaishan volcanic area